Measurement of quarkonium production at forward rapidity in pp collisions at √s = 7 TeV = The ALICE Collaboration: B. Abelev, V. Anguelov, O. Busch, P. Glässel, J. Klein, D. Lohner, X.-G. Lu, A. Maire, J. Mercado Pérez, H. Oeschler, K. Oyama, Y. Pachmayer, K. Reygers, R. Schicker, J. Stachel, J.H. Stiller, M.A. Völkl, J. Wilkinson, B. Windelband, M. Winn, A. Zimmermann [und weitere] - Abelev, Betty; Angelov, Venelin; Busch, Oliver; Glässel, Peter; Klein, Jochen; Lohner, Daniel; Lu, Xianguo; Maire, Antonin; Mercado Pérez, Jorge; Oeschler, Helmut; Oyama, Ken; Pachmayer, Yvonne C.; et al. (The European physical journal. C, Particles and fields, 2014)
The inclusive production cross sections at forward rapidity of J / ψ , ψ ( 2 S ) , Υ (1S) and Υ (2S) are measured in pp collisions at √s = 7 TeV with the ALICE detector at the LHC. The analysis is based on a data sample corresponding to an integrated luminosity of 1.35 pb - 1 . Quarkonia are reconstructed in the dimuon-decay channel and the signal yields are evaluated by fitting the μ + μ - invariant mass distributions. The differential production cross sections are measured as a function of the transverse momentum p T and rapidity y , over the ranges 0 < p T < 20 GeV/c for J / ψ , 0 < p T < 12 GeV/c for all other resonances and for 2.5 < y < 4 . The measured cross sections integrated over p T and y , and assuming unpolarized quarkonia, are: σ J / ψ = 6.69 ± 0.04 ± 0.63 μ b, σ ψ ( 2 S ) = 1.13 ± 0.07 ± 0.19 & μ b, σ Υ ( 1 S ) = 54.2 ± 5.0 ± 6.7  nb and σ Υ ( 2 S ) = 18.4 ± 3.7 ± 2.9, where the first uncertainty is statistical and the second one is systematic. The results are compared to measurements performed by other LHC experiments and to theoretical models.
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 18.09.2020